Desenvolvimento de substrato de ferrita para antenas de microfita - Silva, Pedro Bruno Nogueira da (Universidade Federal Rural do Semi-Árido, 2018)
— This research refers to the synthesis of Nickel Ferrite for application in microstrip antennas. The sizing of the radiant elements of the antenna was adopted as a secondary objective , as well as the simulation of the microstrip antenna in software Ansoft HFSS®. The Sol-Gel process was used to make the ferrite in this work. The results allow the diagnosis of the viability of Nickel Ferrite in microstrip antennas substrate applications.
Artigo Acadêmico
Keywords: Nickel ferrite; Microstrip antennas; Sizing; Simulation; ENGENHARIAS::ENGENHARIA ELETRICA